Pt Single Atom Deposition by Direct Current Sputtering in the Gas-Scattering Regime—A Simple Approach to Controlled Single Atom Loading - Zhou, Xin; Kim, Ji Hyeon; Kim, Hyesung; Zahra, Sani; Schmuki, Patrik (Chemsuschem, 2025)
Supported single atoms represent a new frontier in many catalytic fields, and noble metal single atoms in particular have been reported to be a highly effective cocatalyst in photocatalysis or electrocatalysis. Herein, it is described that direct current sputtering of Pt, when operated under plain gas-scattering conditions, can be leveraged for single atom deposition on various substrates (herein TiO2 and graphene are used as examples). The approach allows a uniform single atom deposition with a high level of control over single atom density and loading amount on both surfaces. Such Pt single atoms on TiO2 can be used directly (without further treatments) as cocatalysts for photocatalytic H2 generation. Remarkably, single atom loading and H2 generation activity correlate linearly over a wide range of Pt loading (0.16–1.41 at%). The findings not only open a new avenue for the synthesis and use of single atoms in photocatalysis but also highlight the use of gas-phase scattering as a simple, scalable, and versatile approach for single-atom catalyst fabrication.
CRIS-Team Scopus Importer:2025-05-23
Keywords: hydrogen generation; photocatalysis; platinum; single-atom catalysis; sputter deposition